Finite Element Analysis for Estimating Strength and Fatigue of the APM Structure - Klabklay Teerawat; Sumpavakup Chaiyut; Khumkrong Asawadech; Thasanavirud Natthikan; Pensuk Pannachai (E3S Web of Conferences)
APM stands for autonomous people mover, which is a mass transit system widely used in many airports to transport passengers between terminals. This article focuses on APM structure newly designed comprising five components namely, chassis, floor, body, roof, and support. The objective of this article is to estimate the strength and fatigue of each component to assess safety. The finite element analysis is implemented to figure out the key results in both static and fatigue load analysis as follows: maximum displacements, maximum stresses and minimum factors of safety in static load, and minimum fatigue life cycles. The grid independence test, which is a significant process in numerical method, is carried out. The results show that the maximum displacements of the chassis, floor, body, roof, and support provide 13.3, 1.13, 0.21, 2.0, and 0.06 millimeters, respectively. The maximum stresses are about 155, 138, 35.9, 167, and 58.2 MPa, respectively, which do not exceed yield strength of material. The minimum factors of safety are about 1.6, 1.8, 7.0, 1.5, and 4.3, respectively, which are in accordance with APM standards. The minimum fatigue life cycles are obtained 1.4, 1.25, 4.81, 1.03, and 2.96 million cycles, respectively, which are not less than the infinite life cycle. Thus, it is obvious that all five components of APM structure are adequate strength and safe to function.